2019
DOI: 10.3390/ijerph16071216
|View full text |Cite
|
Sign up to set email alerts
|

Social Inequalities in Environmental Resources of Green and Blue Spaces: A Review of Evidence in the WHO European Region

Abstract: Residential green and blue spaces and their potential health benefits have received increasing attention in the context of environmental health inequalities, because an unequal social distribution of these resources may contribute to inequalities in health outcomes. This systematic review synthesised evidence of environmental inequalities, focusing on availability and accessibility measures of green and blue spaces. Studies in the World Health Organisation (WHO) European Region published between 2010 and 2017 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(63 citation statements)
references
References 64 publications
5
55
1
2
Order By: Relevance
“…Ecological studies consistently show that deprived areas have lower green space availability than more affluent areas. However, associations in cross-sectional studies on the individual level were mixed and dependent on the type of socio-economic indicator and the green space measures applied [77]. Despite having greater access to public green space, those with higher educational attainment complained more often about lack of access to recreational or green areas than those with lower levels of education [75].…”
Section: Resultsmentioning
confidence: 99%
“…Ecological studies consistently show that deprived areas have lower green space availability than more affluent areas. However, associations in cross-sectional studies on the individual level were mixed and dependent on the type of socio-economic indicator and the green space measures applied [77]. Despite having greater access to public green space, those with higher educational attainment complained more often about lack of access to recreational or green areas than those with lower levels of education [75].…”
Section: Resultsmentioning
confidence: 99%
“…They found that the higher-income groups within this region generally had better access to environmental amenities, especially to public greenspace, while the lower-income groups lived in places with somewhat lesser environmental quality. More recently, Schüle and others concluded that this was also the case in several other European countries [26]. However, high-income groups do not always have more greenspace nearby.…”
Section: Previous Studies On Inequalities In Access To Greenspacementioning
confidence: 89%
“…In conformity with the other two systematic reviews on environmental inequalities [19,23] we defined in this review a descriptive analysis as a provision of quantitative resource measures across social dimensions in a cross table without performing a statistical test. We compared the highest to the lowest social group in order to assess if environmental inequalities exist or not.…”
Section: Methodsmentioning
confidence: 99%